THE FEATURES OF THE LEFT VENTRICLE REMODELING IN PATIENTS WITH SYMPTOMATIC HYPERTENSION ON THE GOUT BACKGROUND AND THE TREATMENT OPTIMIZATION - Данюк, І.О. (World of Medicine and Biology, 2015)
Gout is the most common cause of inflammatory arthritis in men elder than 30 years. Hypertension is diagnosed in about 80 % of patients with gout. Left ventricle (LV) remodeling is the logical process of myocardium restructuring in patients with hypertension. Aim of research. The aim of the study was to determine the structural parameters of the LV in patients with gout and symptomatic hypertension and to assess the effect of angiotensin receptor blocker II and calcium channel blocker combination on the process of reverse LV remodeling. Material and methods. We studied 50 men with primary gout, which combined with hypertension syndrome, 30 men with essential hypertension and 20 healthy men. The first and the second groups were comparable in duration and degree of hypertension. We determined the main basic parameters of LV, using ECHO-CS. Index of myocardial mass of the LV and the relative wall thickness have been calculated for researching LV geometry. We used the combination of losartan and lercanidipine for hypertension correction in patients with gout for 24-weeks. Statistic assessment of the figures obtained has been carried out by the programs STATISTICA 6.0. The difference between the variables was statistically significant at a level of significance test p